Designation of a lectotype for the Canestrini's Goby, Gobius canestrinii Ninni, 1883 (Teleostei, Gobiiformes, Gobiidae, Gobionellinae) - Ahnelt, Harald; Tougard, Christelle; Kovačić, Marcelo (2021)
A recent study based on molecular biological data revealed that Gobius canestrinii (Ninni, 1883), a gobioid fish endemic to the Adriatic basin, has to be split in three lineages. The original description was based on populations from two distant localities in Italy and in Croatia respectively, the first representing one of these lineages, the second most likely belonging to another lineage. To fix the name of the species, we hereby designated a lectotype for Canestrini"s Goby.
Nedavna istraživanja, zasnovana na molekularno biološkim metodama, otkrila su da se Gobius canestrinii (Ninni, 1883), endemski glavoč jadranskog bazena, dijeli u tri filogenetske grane. Izvorni opis vrste zasnivao se na populacijama dva udaljena lokaliteta u Italiji i Hrvatskoj. Populacija u Italiji predstavlja jednu od tri filogenetske grane, dok druga najvjerojatnije predstavlja jednu od preostale dvije grane. Da bi se fiksiralo ime vrste, u ovom radu određujemo lektotip Canestrinijevog glavoča.
Bibliografija: str. 47-48.
Summary ; Sažetak.
Keywords: Ribe -- Glavoč -- Gobiidae -- Gobius canestrinii -- Taksonomija -- Lektotipizacija; Venecija -- Italija